1983
DOI: 10.1266/jjg.58.315
|View full text |Cite
|
Sign up to set email alerts
|

Metaphase chromosome configuration of the immigrans species group of Drosophila.

Abstract: Metaphase chromosome configurations of 23 species and subspecies belonging to five subgroups of the immigrans species group of Drosophila were examined by the Giemsa staining method, from the point of view of the phylogenetic relationships in this species group.New to science are the descriptions of the karyotypes of five species, Taxon-C, Taxon-F, D, nivei f rons,, D. quadrilineata and D, neohypocausta which are 2n=8, 2R+1V+1D; 2n=8, 2R+1V+1D; 2n=8, 2R+1V+1D; 2n =12, 4R+ 1V+ 1D; and 2n = 6, 2R+ 1V, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…However, there is a striking difference in karyotypes between the two. The basic karyotype of this group is 1V + 2R + 1D (ie, 2n = 8), yet from among all members of this group, only D albomicans has 2V + 1D (2n = 6), a result of fusions of the third and the sex chromosomes (Wakahama and Kitagawa, 1972;Wakahama et al, 1983). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a striking difference in karyotypes between the two. The basic karyotype of this group is 1V + 2R + 1D (ie, 2n = 8), yet from among all members of this group, only D albomicans has 2V + 1D (2n = 6), a result of fusions of the third and the sex chromosomes (Wakahama and Kitagawa, 1972;Wakahama et al, 1983). …”
Section: Introductionmentioning
confidence: 99%
“…David and Tsacas (1981) (Wilson et al, 1969;Wakahama et al, 1983;Hatsumi, 1987 (Inoue and Kitagawa, 1974;1975) …”
Section: Introductionmentioning
confidence: 99%
“…This implies that the distribution expansion of D. albomicans is likely attributed to the intraspecific variation including such strains that have a high cold tolerance and a strong acclimation response. It is noteworthy that D. pallidifrons, which is the most ancestral species in the D. nasuta subgroup (Wakahama et al, 1983;Suzuki et al, 1990), showed a relatively high cold tolerance after the cold acclimation (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…From the beginning of the pioneering work of Wilson et al, (1969), phylogeny of the nasuta subgroup has been extensively studied at various levels of organiEdited by Masatoshi Yamamoto * Corresponding author. E-mail: drosrang@sancharnet.in zations namely, morphophenotypes (Nirmala and Krishnamurthy, 1972), hybridization and hybrid sterility (Ramachandra and Ranganath, 1988), karyotypes (Ranganath and Hägele, 1981;Wakahama et al, 1983;Ranganath and Ushakumari, 1987;Rao and Ranganath, 1991), hybrid salivary chromosomes (Lambert, 1978;Rajasekarasetty et al, 1980), heterochromatin and satellite DNA (Ranganath et al, 1982;Ranganath and Ushakumari, 1987), isozymes and allozymes (Kanapi and Wheeler, 1970;Ramesh and Rajasekarasetty, 1980), glue proteins (Ramesh and Kalisch, 1989), courtship patterns (Tanuja et al, 2001), courtship song (Shao et al, 1997), mitochondrial DNA (Chang et al, 1989;Yu et al, 1999), and male accessory gland proteins (Ram and Ramesh, 2001).…”
Section: Introductionmentioning
confidence: 99%